PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS REALISTIC MATHEMATIC EDUCATION (RME) UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Irfan Supriatna; Victoria Karjiyati; Salati Asmahasanah (ALGORITMA: Journal of Mathematics Education, 2021)
This study aims to produce student worksheets (LKPD) using the Realistic Mathematics Education (RME) approach to cultivate critical thinking skills in grade IV elementary school (SD) which can be used as a teacher guide in making student worksheets. This research is a Research and Development (R&D) research by modifying the 4-D model. However, this research was only carried out until the third stage, namely the Develop stage. Validation is carried out by material experts, linguists, and design experts. The data analysis used descriptive statistical analysis on the results of expert validation assessments and teacher responses and qualitative descriptive analysis on comments from expert validation and teacher responses. This study produced LKPD based on RME to foster mathematical critical thinking skills with an assessment from material experts, linguistic expert, design expert, and the teacher's response with a very valid category. Furthermore, the results of a limited trial get an average value of 80.2 with 100% completeness.